Learner Autonomy in Team-Based Learning : A Case Study of Mechanical Engineering Education - Lin, Yu-Sheng; Lin, Yu-Hsuan (Journal of Engineering Education Transformations, 2023)
Team-based learning (TBL) has been increasingly applied in engineering and science education over the past decade. This study explores a particular TBL approach used in a mechanical engineering module for second-year undergraduates in Taiwan. The results of a survey on these students’ learner autonomy (LA), perceptions of TBL, engagement with TBL, self-reported contributions and concerns about TBL activities were analyzed along with their academic performance. The results suggested that LA played a crucial role in TBL, especially contribution to group work, and that classroom implementations should therefore make it a priority to boost LA. In addition, positive reciprocity was found to be operating during group work. Group differences were found in issues the students expressed concern about. Students who cared about fairness had higher LA and were more likely to contribute to team tasks whilst some students could have been less engaged in group activities due to poor organizational structure. Several challenges were also observed in this study. They included passive learners, classroom-management problems, free-riding, and limited resources. Based on our findings, we recommend that engineering instructors encourage student-teacher communication by using bonus-point incentives, student experts, peer evaluation and group competitions.